Construction of hierarchically porous carbon from plastic waste for CO2 capture and separation. (March 2023) - Wang, W.; Wang, Z.; Jiang, L.; Shen, X.; Wang, Y.; Zhu, R.; Shen, Z.; Xu, X.; Liu, Y.; Li, X.; Wang, J.
Abstract: Greenhouse effect arising from excessive atmospheric CO2 amount and white pollution caused by plastic waste are aggravating the growing ecological crisis. The use of plastics as precursors for the construction of porous carbon adsorbents for CO2 capture is considered a potential win–win strategy to improve environmental problems. Here, porous carbon materials with high porosity were obtained from plastic polyethylene terephthalate as a precursor using different activators under varying carbonization temperatures. Notably, KOH-900 exhibited a significant Brunauer-Emmett-Teller (BET) surface area of 3090 m 2 /g as well as high pore volume of 1.931 cm 3 /g, respectively. More importantly, at 273 K and 1 bar, the CO2 uptake amount of KOH-700 was determined to be 6.23 mmol/g. These porous carbon materials hold appealing promise in CO2 adsorption and separation, and this research may contribute to improve the increasingly serious greenhouse effect and realize the resource utilization of plastics. Graphical abstract: A series of highly porous carbons from plastic polyethylene terephthalate as a precursor using different activators under varying carbonization temperatures were prepared. The boosted porosity and significant microporous textures of such materials facilitate superior CO2 capture and separation property. Image 1 Highlights: A series of highly porous carbon materials from plastic polyethylene terephthalate were synthesized. KOH-700 exhibits significant surface area of up to 3090 m 2 /g and total pore volume as much as 1.931 cm 3 /g. KOH-700 shows an excellent CO2 capture capacity of 6.23 mmol/g at 273 K and 1 bar. These obtained materials are capable of selective adsorption of CO2 over N2 . This study may pave a new way for mitigating environmental crisis by realizing the recycling of plastic waste